Manajemen Sumber Daya Lingkungan Sekolah dalam Meningkatkan Pola Hidup Bersih dan Sehat (PHBS) Peserta Didik (Studi Kasus di Sekolah Menengah Pertama (SMP) Yayasan Wanita Kereta Api (YWKA) Bandung) - Deti Rostini; Cucu Amirah; Puji Rahayu; Rizky Juliansyah; Sandi Sopandi (Departement of Mathematics Education, 2023)
This research was conducted to find out an overview based on empirical findings in the management of school environmental resources, especially in improving students' PHBS. This research uses case studies where the process of seeking information through the phenomena that occur. This study also uses data collection techniques through observation, interviews and documentation studies. The results obtained are that environmental resource planning is reflected in the school's vision and mission, organizing is reflected in the school's organizational structure, the implementation of environmental resource management including the implementation of the vision, mission and goals of the school is carried out by the field of developers and school members, resource development through participation training activities and programs related to cleanliness as well as evaluation and follow-up which are carried out with direct supervision from the school principal in the form of sudden inspections of school education staff carried out conditionally and maintaining the environment of school residents. Based on the results of this study, it can be concluded that management of school environmental resources has been carried out according to its function, but it is necessary to make a program of environmental resource management activities related to planned PHBS so that a school environment that supports the comfort and health of students is created.